Food and sustainability in the twenty-first century : cross-disciplinary perspectives - Collinson, Paul, 1969-; Young, Iain; Antal, Lucy; Macbeth, Helen (Anthropology of food and nutrition., 2019)
"Sustainability is one of the great problems facing food production today. Using cross-disciplinary perspectives from international scholars working in social, cultural and biological anthropology, ecology and environmental biology, this volume brings many new perspectives to the problems we face. Its cross-disciplinary framework of chapters with local, regional and continental perspectives provides a global outlook on sustainability issues. These case studies will appeal to those working in public sector agencies, NGOs, consultancies and other bodies focused on food security, human nutrition and environmental sustainability"--